A new species of Trachelas L. Koch, 1872 (Araneae, Trachelidae) from Tajikistan - Yuri M. Marusik; Alexander A. Fomichev (Pensoft Publishers, 2022)
A new species of trachelid spiders, Trachelas crewsae sp. nov. is described from south-western Tajikistan based on both sexes. The new species is closely related to T. vulcani Simon, 1896 from South-East Asia but differs in the conformation of the copulatory organs and color pattern.